Racism, the Immigration Enforcement Regime, and the Implications for Racial Inequality in the Lives of Undocumented Young Adults. Issue 1 (January 2015) - Aranda, Elizabeth; Vaquera, Elizabeth
The current immigration enforcement regime embodies a colorblind racial project of the state rooted in the racial structure of society and resulting in racism toward immigrants. Approaching racism from structural and social process perspectives, we seek to understand the social consequences of enforcement practices in the lives of undocumented immigrant young adults who moved to the United States as minors. Findings indicate that although legal discourse regarding immigration enforcement theoretically purports colorblindness, racial practices such as profiling subject immigrants to arrest, detention, and deportation and, in effect, criminalize them. Further, enforcement practices produce distress, vulnerability, and anxiety in the lives of young immigrants and their families, often resulting in legitimate fears of detention and deportation since enforcement measures disproportionately affect Latinos and other racialized immigrant groups in U.S. society. We conclude that policies and programs that exclude, segregate, detain, and physically remove immigrants from the country reproduce racial inequalities in other areas of social life through spillover effects that result in dire consequences for these immigrants and their kin. We argue that immigrant enforcement practices reflect the nation's racial policy of our times.